Returns to Education and Human Capital Externalities: Empirical Evidence from Indonesia - Purnastuti, Losina (Curtin University, 2011)
This thesis investigates the return to schooling and human capital externalities in Indonesia. It is found that estimated returns to schooling in Indonesia are substantially non-linear and considerably lower than in other Asian countries and developing countries. Furthermore, the findings provide evidence that human capital spillovers exist in Indonesia and support the view that investing in education is even more important for aggregate economic performance than it is for the individuals who do so.